Potensi Implementasi Fair Trade dan Studi Kasus di Indonesia - Felix, Michael (Universitas Medan Area, 2024)
Fairtrade, a trade system, seeks to facilitate improved and enduring trading circumstances for producers in developing nations. This article examines the implementation of Fair Trade in Indonesia, including the encountered hurdles, and explores the influence of economic and social elements on the process. This article aims to evaluate the execution and obstacles of Fair Trade in Indonesia, focusing on the economic and social aspects that may impede the progress. The primary concerns identified include the uneven implementation of fairtrade principles and practices in different countries, as well as the challenges in increasing public knowledge and approval of the concept. The analysis of these issues employs Alexander Wendt's constructivist theory to comprehend the social dynamics and social construction associated with fair trade. The data were gathered via literature research and document analysis on fair trade in Indonesia. The results indicate that while fair trade can be a positive catalyst for change, its execution is hindered by corrupt practices, intricate certification procedures, and a dearth of public knowledge. To achieve the intended efficacy, it is necessary to implement policy reforms and enhance compliance with fair trade principles.